Disease Progression in a Patient With Indolent T-Cell Lymphoproliferative Disease of the Gastrointestinal Tract. (February 2019) - Perry, Anamarija M.; Bailey, Nathanael G.; Bonnett, Michelle; Jaffe, Elaine S.; Chan, Wing C.
Indolent T-cell lymphoproliferative disorder (T-LPD) of the gastrointestinal (GI) tract is a new provisional entity in the 2016 revision of the World Health Organization classification. The disease has an indolent course and progression to aggressive T-cell lymphoma has rarely been reported. We describe a case of a 37-year-old male with indolent T-LPD of the GI tract who 3 years later developed aggressive T-cell lymphoma and died of progressive disease. An infiltrate of indolent T-LPD in the GI tract and aggressive lymphoma diagnosed from the liver biopsy had similar immunophenotype, but cellular infiltrate in the liver showed more atypia compared with the GI biopsies of indolent T-LPD. Moreover, T-cell gene rearrangement studies showed an identical clonal rearrangement in indolent T-LPD and aggressive lymphoma. Patients with indolent T-LPD of the GI tract need a long-term follow-up, as some of them may develop more aggressive lymphoma.